Implementasi Metode SOSTAC Pada Strategi Digital Marketing Di UMKM Coklat VIP Pontianak - Mamase, Adiyath Randy Yudi; Hidayati, Asri; Depriyani, Magdalena (Universitas Jambi, 2024)
This study aims to design and implement a digital marketing strategy using the SOSTAC model for the VIP Chocolate MSME to expand its market reach and increase profitability. The conceptual framework of this study refers to the SOSTAC model, which consists of six stages: Situation Analysis, Objectives, Strategy, Tactics, Actions, and Control. The research methods include observation, interviews, documentation, and literature review. Based on the results, it can be concluded that an economical promotional campaign with a total cost of IDR 3,600,000 over a three-month period through Facebook and Instagram significantly improved the social media reach and profitability of VIP Chocolate MSME. The campaign reached a total of 214,635 accounts on Facebook and 582,301 on Instagram. Post interactions totaled 1,362 on Facebook and 2,615 on Instagram. Additionally, the number of page followers increased to 20 on Facebook and 705 on Instagram.